Decade of the dead [videorecording (DVD)] - Patrick-Thomas, Sean; Green, Jenna Leigh; Johnson, Shane, 1976- (Darkstar Pictures, 2024)
Ten years into the zombie apocalypse, Rachel, Tweeter, and Ben, live in a world without hope. While scavenging the Caribbean, they happen upon The Sworn, a zombie-worshiping cult of the worst remnants of humanity. The Sworn not only worship the dead but consume the living and enslave those they fail to convert. Rachel is captured and reunited with her long-lost sister, the high priestess of The Sworn, who leads the cult with Grinner, a blood-thirsty, fanatical brute, but the reunion is short-lived as they battle to make it off the island alive.